Two new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from Southern France - Vinçon, Gilles; Launay, Bertrand; Reding, Jean-Paul G. (Zootaxa, 2021)
Two new species of Protonemura Kempny, 1898, P. lupina sp. n., from the Castellane Prealps and the southern Mercantour region in the French Maritime Alps, and P. alexidis sp. n., from the southern flank of the Massif Central, are described, illustrated, and compared to their closest relative species P. risi (Jacobson & Bianchi, 1905) and P. spinulosa (Navás, 1921). Information on distribution and ecological preferences of these new species is provided.